2013
DOI: 10.3109/09553002.2014.859765
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic and inflammatory effects of plutonium-nitrate retention in an exposed nuclear worker and beagle dogs

Abstract: The data suggests that FASLG, BCL2, CASP3 and apoptosis play a role in the inflammatory responses following prolonged plutonium exposure. Utilizing these unique tissues revealed which pathways are triggered following the internal deposition and long-term retention of plutonium-nitrate in a human and a large animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The TUNEL assay revealed an elevation of apoptosis in the tracheal mucosa, tumor cells, and nuclear debris in the alveoli and lymph nodes of the beagles with statistically significant modifications in Fas ligand, B-cell lymphoma 2, and caspase-3 expression. It is of note that a comparably exposed human subject in the same study did not develop pulmonary tumors or display an elevated rate of apoptosis in lung tissues [35].…”
Section: Animal Studiesmentioning
confidence: 64%
“…The TUNEL assay revealed an elevation of apoptosis in the tracheal mucosa, tumor cells, and nuclear debris in the alveoli and lymph nodes of the beagles with statistically significant modifications in Fas ligand, B-cell lymphoma 2, and caspase-3 expression. It is of note that a comparably exposed human subject in the same study did not develop pulmonary tumors or display an elevated rate of apoptosis in lung tissues [35].…”
Section: Animal Studiesmentioning
confidence: 64%
“…A retrospective study of 326 plutonium-exposed and 194 unexposed Rocky Flats Plant nuclear workers (Newman et al 2005) The long-term retention of plutonium in the upper respiratory tract of USTUR Case 0269 can be explained by an assumption of a small bound fraction (Puncher et al 2017a, Birchall et al 2019. However, autoradiography and histologic examination of the tissue samples from this individual's lung (Nielsen et al 2012(Nielsen et al , 2014 indicate otherwise. First, autoradiography showed alpha stars indicative of aggregated plutonium localised within the connective tissue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, Nielsen et al (2012) reported that fibrotic scar tissue effectively encapsulated a portion of plutonium preventing its clearance from the body. Nielsen et al (2014) reported that a fraction of the initially deposited plutonium nitrate was 'either transformed into an insoluble colloid or 'bound' within pockets of connective scar tissue in the lung in its initial form'. Because binding-as defined by the ICRP-occurs after dissolution, the material in the bound compartments is not predicted to be in its initial form.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, the relevance of selecting a murine genetic background (even if inbred) that will not interfere with the issue of interest (e.g., Bourdi et al, 2011; Ulmasov et al, 2013), and still be reasonable breeders with relatively good health. Looking beyond the traditional murine models to uncover human-like diseases opens the door to collaborations between veterinarians and basic researchers (for example, Vernau et al, 2013) and explore new therapies (Patel et al, 2011; Nielsen et al, 2014), including the use of stem cells (Volk and Theoret, 2013) and “personalized medicine” (Palotie et al, 2013). Across-species studies fall under the umbrella named “One Health” initiative, which since 1984 combines human, animal, and environmental components to addressing global health challenges (Bidaisee and Macpherson, 2014).…”
Section: On the Organism Of Choice: Welcome To The Battlegroundmentioning
confidence: 99%